Crushing of braced tubes - Ho, Teng Chye. (2010)
The aim of this project is to study the energy absorption capabilities of thin-walled tubes with various cross sectional geometry. 6 tubes of mainly circular, square and hexagonal shapes were studied. 2 of the circular tubes had 2 and 3 reinforcement lines in the middle whereas 1 of the square tubes had 2 reinforcement lines in the middle.